War crimes trial in Bangladesh: a real political Vendetta - Jalil, Md. Abdul (Canadian Center of Science and Education, 2010)
According to national and international press report, the present Awami League (AL) government in Bangladesh has been oppressing opposition political party leaders and their supporters as a means of revenge against them since it assumed in power in January 2009. So far it has killed more than 200 people extra-judicially and arrested more than 1200 leaders and supporters of Jamaat-e-Islami Bangladesh (Jamaat) and Shibir without any valid reason and they are being oppressed in detention since February 2010. This paper mainly focuses on the war crimes trial issue in Bangladesh for war crimes committed in 1971 during independence movement in Bangladesh. Descriptive and analytical research methodology has been applied in this paper. It is an empirical research. It critically explains the mala fide intention of the AL government in prosecuting and arresting some of the opposition political party leaders in Bangladesh for their alleged role in 1971.